Autocratic, Democratic and Free-Controlled Leadership Styles Have a Simultaneous Influence On Employee Performance: Case Study Of PT. Mandom Indonesia Tbk Surabaya Branch - Achmad Daengs GS (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In a company, human resources are considered the most important and determine the success of a company, humans act as managers of the production factors used in company operations. Human resources in a company are said to be unique because basically humans find it difficult to free themselves from conflicts of interest such as the interests of the organization and the interests of the individual himself. It is impossible for a company to operate its activities without humans. No matter how simple a company is, human resources are the core of the company's activities so that the company is the result of activities of humans by humans and for humans. Human resources that support the smooth achievement of company goals are employees who have the ability to work well, have initiative, creativity, high responsiveness and the ability to carry out assigned tasks effectively. Managing human resources really depends on the character of the leader. Leadership style greatly influences the achievement of an organization's goals, where it influences employee performance. Therefore, a company definitely needs a leadership role in controlling the company to achieve common goals. This can be used as a consideration for the company which will later influence decision making and every company policy. The problem in this research is: is there an influence of autocratic, democratic and control-free leadership styles on the performance of PT employees. Mandom Indonesia Tbk Surabaya Branch? The data used in this research is primary data obtained by distributing questionnaires to PT employees. Mandom Indonesia Tbk Surabaya Branch.